H-mode operation in helium plasma with tungsten divertor and low input torque in EAST. (21st July 2020) - Zhang, B.; Gong, X.; Qian, J.; Ding, R.; Huang, J.; Sun, Y.W.; Gu, X.; Li, Y.Y.; Gao, W.; Yu, Y.W.; Li, M.H.; Sun, Z.; et al.
Abstract: To support the ITER early non-nuclear operational phase, recent helium experiments have been investigated intensively in the superconducting tokamak EAST equipped with ITER-like Tungsten divertor, under the condition of low injected torque. This paper demonstrates experimental observations from these experiments. In particular, we report the impact of helium concentration on the L-H transition power threshold, energy confinement, and the ELM behavior. Dependences of L-H threshold on electron density, plasma current and magnetic field are also discussed.